2022
DOI: 10.3390/cells11101629
|View full text |Cite
|
Sign up to set email alerts
|

Cytochalasin B Modulates Nanomechanical Patterning and Fate in Human Adipose-Derived Stem Cells

Abstract: Cytoskeletal proteins provide architectural and signaling cues within cells. They are able to reorganize themselves in response to mechanical forces, converting the stimuli received into specific cellular responses. Thus, the cytoskeleton influences cell shape, proliferation, and even differentiation. In particular, the cytoskeleton affects the fate of mesenchymal stem cells (MSCs), which are highly attractive candidates for cell therapy approaches due to their capacity for self-renewal and multi-lineage diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 95 publications
(115 reference statements)
4
24
0
Order By: Relevance
“…The reorganization of the actin cytoskeleton plays a crucial role during stem cells differentiation [22,40,41]. A large number of studies have shown that there is an inverse relationship between actin polymerization and adipogenesis, whereas there is a direct correlation between actin polymerization and osteogenesis [27,28,[42][43][44]. The dynamic nature of the actin cytoskeleton is determined by the actions of numerous actin-binding proteins, such as cofilin, profilin, CapZ, Arp2/ 3, and Ena/VASP family [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The reorganization of the actin cytoskeleton plays a crucial role during stem cells differentiation [22,40,41]. A large number of studies have shown that there is an inverse relationship between actin polymerization and adipogenesis, whereas there is a direct correlation between actin polymerization and osteogenesis [27,28,[42][43][44]. The dynamic nature of the actin cytoskeleton is determined by the actions of numerous actin-binding proteins, such as cofilin, profilin, CapZ, Arp2/ 3, and Ena/VASP family [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a less-organized and less-stiff actin cytoskeleton has been found to act as a necessary prerequisite to differentiate mesenchymal stem cells into adipocytes. 42 , 43 , 44 By the aid of AFM, coupled with gene expression and metabolic pattern analyses, we have recently shown that CB could be used to afford a fine-tuning of nanomechanical properties in human, adipose-derived MSCs (AD-MSCs), deeply affecting their metabolism, proliferation, and morphology. In particular, CB elicited a dose-dependent reduction in metabolic activity, associated with remarkable changes in acting organization, focal adhesions subcellular redistribution patterning, and stem cell shape.…”
Section: Cytoskeletal Mechanics and (Stem) Cell Heterogeneitymentioning
confidence: 99%
“…In particular, CB elicited a dose-dependent reduction in metabolic activity, associated with remarkable changes in acting organization, focal adhesions subcellular redistribution patterning, and stem cell shape. 42 The functional implications in the stem cell heterogeneity potential of such tuning of cell stiffness and viscoelastic properties could be inferred by the capability of CB of inducing a marked metabolic switch toward an adipogenesis program, highlighted by the expression and subcellular localization of PPAR-γ, and C/EBP-α, by the overexpression of perilipin, and by the appearance of typical lipid vacuoles, positively stained with ORO solution. 42 Modulation of biomechanical dynamics at the level of actomyosin network and adhesion complexes has proven effective in the orchestration of multicellular development of human embryonic stem cells and neuroprogenitor cells.…”
Section: Cytoskeletal Mechanics and (Stem) Cell Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was discovered that the cytoskeletal network is crucial to direct cell shape, proliferation, senescence, and differentiation by influencing mechano-sensing and mechano-transduction pathways [ 17 , 18 , 19 ]. Particularly, the cytoskeleton may act on MSC fate, as can be demonstrated by changes in mechanical properties detected during specific commitment of hMSCs [ 17 , 20 , 21 , 22 ]. For instance, under adipogenic commitment, MSCs lose and disorganize their cytoskeletal framework, taking a round shape and disassembling the focal adhesions.…”
Section: Introductionmentioning
confidence: 99%